Blocking of p38 and transforming growth factor β receptor pathways impairs the ability of tolerogenic dendritic cells to suppress murine arthritis. Issue 1 (27th December 2012) - Gárate, David; Rojas‐Colonelli, Nicole; Peña, Corina; Salazar, Lorena; Abello, Paula; Pesce, Bárbara; Aravena, Octavio; García‐González, Paulina; Ribeiro, Carolina H.; Molina, María C.; Catalán, Diego; Aguillón, Juan C.
Abstract: Objective: Dendritic cells (DCs) modulated with lipopolysaccharide (LPS) are able to reduce inflammation when therapeutically administered into mice with collagen‐induced arthritis (CIA). The aim of this study was to uncover the mechanisms that define the tolerogenic effect of short‐term LPS‐modulated DCs on CIA. Methods: Bone marrow–derived DCs were stimulated for 4 hours with LPS and characterized for their expression of maturation markers and their cytokine secretion profiles. Stimulated cells were treated with SB203580 or SB431542 to inhibit the p38 or transforming growth factor β (TGFβ) receptor pathway, respectively, or were left unmodified and, on day 35 after CIA induction, were used to inoculate mice. Disease severity was evaluated clinically. CD4+ T cell populations were counted in the spleen and lymph nodes from inoculated or untreated mice with CIA. CD4+ splenic T cells were transferred from mice with CIA treated with LPS‐stimulated DCs or from untreated mice with CIA into other mice with CIA on day 35 of arthritis. Results: Treatment with LPS‐stimulated DCs increased the numbers of interleukin‐10 (IL‐10)–secreting and TGFβ‐secreting CD4+ T cells, but decreased the numbers of Th17 cells. Adoptive transfer of CD4+ T cells from treated mice with CIA reproduced the inhibition of active CIA accomplished with LPS‐stimulated DCs. The therapeutic effect of LPS‐stimulated DCs and their influence on T cell populations were abolished when the p38 and the TGFβ receptor pathways were inhibited. Conclusion: DCs modulated short‐term (4 hours) with LPS are able to confer a sustained cure in mice with established arthritis by re‐educating the CD4+ T cell populations. This effect is dependent on the p38 and the TGFβ receptor signaling pathways, which suggests the participation of IL‐10 and TGFβ in the recovery of tolerance.